2014
DOI: 10.1136/openhrt-2014-000047
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary intervention causes a rapid but transient mobilisation of CD34+CD45cells

Abstract: ObjectiveCirculating CD34+CD45− cell concentrations are increased in patients with coronary artery disease, however their pathophysiological significance is unknown. We determined CD34+CD45− cell concentrations following percutaneous coronary intervention (PCI) in order to explore their role in acute vascular injury.MethodsIn a prospective time-course analysis, we quantified using flow cytometry circulating CD34+CD45− cells, traditional CD34+VEGFR-2+ putative endothelial progenitor cells (EPCs), CD14+ VEGFR− 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…24 Mobilization of CD34 + and CD133 + cells has been reported previously in response to large nonspecific inflammatory insults [25][26][27] and myocardial infarction 28,29 whereas cellular response to discrete vascular injury is less readily demonstrable. 30,31 Acute mobilization of CD34 + populations has, however, been described after PCI, with higher concentrations predicting restenosis. 28,32 Alongside the disappointing injury.…”
Section: Discussionmentioning
confidence: 99%
“…24 Mobilization of CD34 + and CD133 + cells has been reported previously in response to large nonspecific inflammatory insults [25][26][27] and myocardial infarction 28,29 whereas cellular response to discrete vascular injury is less readily demonstrable. 30,31 Acute mobilization of CD34 + populations has, however, been described after PCI, with higher concentrations predicting restenosis. 28,32 Alongside the disappointing injury.…”
Section: Discussionmentioning
confidence: 99%
“…Only rare studies are available on inflammatory answer in patients with coronary angiogram without PCI. In a study on only 13 patients without PCI, CRP was unchanged by contrast with patients with PCI (n=23; P<0.002) [12] . In another small study, CRP as well as other inflammatory proteins elevated 24 and 48 hours after PCI in 40 patients with stable angina [13] .…”
Section: Discussionmentioning
confidence: 92%
“…This partially agrees with Padfield et al that described the same kinetics for circulating CD34+, CD45− cells, but not for CD34+, KDR+ cells. [17] More recently, Gao et al have found the same EPC kinetics than us during the first 24 h post-PCI for CD133+, CD34+, KDR+ cells. [18] They also described that EPC mobilisation is influenced by the degree of endothelial injury.…”
mentioning
confidence: 73%